Parametrical study of the cementitious materials degradation under external sulfate attack through numerical modeling. (1st June 2016) - Soive, Anthony; Roziere, Emmanuel; Loukili, Ahmed
Highlights: Numerical simulations were used to improve the design of sulfate attack testing. Aluminate and sulfate are considered in order to understand the cracks mechanism. Great influence of boundary conditions on degradation rate and the formed products. Abstract: Underground concrete structures may be subjected to external sulfate attack and their long-term performance is of concern. A coupled transport/chemical numerical model has been compared to experimental data obtained on a cement paste exposed to external sulfate attack thanks to recent developments in experimental analysis such as scanning electron microscopy and image analysis that provided total ion concentration profiles for a given species in cement paste specimens. As other studies the model succeeded in calculating the position of the ettringite precipitation front and the position of the first decrease due to the portlandite dissolution whereas the leaching of portlandite and ettringite was not accurately assessed in the first millimeters because of the necessity to take into account change of the transport properties in the degraded zone. Then a numerical parametric study was carried on. The influence of permanent solution renewal, pH control, and dissolved CO2 concentration were analyzed. The accelerating effect of permanently renewing the solution was confirmed. The influence of the pH control was found dependent of the renewing of solution. The presence of CO2 did not play a significant role.